Оценка параметров SIP-сети с использованием раскрашенных сетей Петри - Кузьминых, Е. Д. (Проблеми телекомунікацій, 2012)
The Petri model of call setup and disconnect in SIP network is worked out. This model allows to evaluate the timed and probability characteristics of signaling traffic and the dynamics of server buffer utilization.
Keywords: SIP-сеть; SIP-сервер; время установления соединения; раскрашенные сети Петри